Pengaruh Agama Islam terhadap Kesehatan Mental Penganutnya - Iklima Salji; Inas Dhia Fauziah; Nabila Salma Putri; Najwa Zalfa Zuhri (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The development of time and social changes have an influence on the social activities of the community. Lifestyle, views, communication, and so on bring new problems in life. This will have an impact on a person's mental health condition. For a Muslim, religion has a big role in overcoming problems in his life. This study aims to explain how the implementation and influence of Islam on the mental health of a Muslim. Purposive sampling technique is the method used in this study. The results of the study show that Islam and mental health have a good correlation in overcoming one's emotional problems. Because, what is contained in the teachings of Islam contained in the Al-Quran and As-Sunnah is in accordance with human nature.